Kajian Sistematik Teologi Mengenai Personalitas Iblis: Periode Media-Persia Sampai Kepada Injil [Systematic Theology Review on the Personhood of the Devil: Media-Persia Period up to the Gospel] - Christar Arstilo Rumbay; Roger Parengkuan (Diligentia: Journal of Theology and Christian Education, 2021)
The personality of Satan shares massive discussion together with fluctuation. The debate plays surround his figurity and personality. Biblical period denotes distinct knowledge. This essay attempts to delve and explore the personality of Satan in the period of Midian-Persian to New Testament time especially in the Gospel. This research is a qualitative work that occupying literatures, articles and books to re-construc the personality of Satan. As the result,  the sociological infuences of Midian-Persian significantly contribute the knowledge of God’s people. They considers Satan as a symbol of war enmity. Further, in the Gospel period, Bible writters supply various of personality to describe Satan’s existence.